Sequestration of Vitamin E by Liver Fat in vivo, in vitro and in Women with Hepato-steatosis. (29th May 2020) - Violet, Pierre-Christian; Ebenuwa, Ifechukwude; Chung, Stacey; Atkinson, Jeffrey; Manor, Danny; Levine, Mark
Abstract: Objectives: Hepato-steatosis (HS) due to obesity is now the most common cause of chronic liver disease in the Americas and Western Europe. The only means to prevent disease is avoidance of obesity. α-Tocopherol at doses of 800 I.U. daily was reported to have partial treatment effects for NASH. Because alpha tocopherol is a fat-soluble vitamin, we hypothesized that excess fat in liver, as found in HS, could act unintentionally sequester vitamin E, thereby altering its normal physiology and contributing to development of NASH. Using oral and intravenous deuterated tocopherols, evidence showing HS altered a-tocopherol physiology was reported based on pharmacokinetics studies in obese women with HS. Here we further tested the sequestration hypothesis in vitro, and in vivo . Methods: In vitro, we investigated effects of fat on intracellular vitamin E localization. Control human and mouse hepatocytes and hepatocytes pre-loaded with fat were incubated with fluorescent α-tocopherol (BDP-α-tocopherol). In vivo experiments were performed using mice fed a high fat diet with different vitamin E doses. Results: Compared to controls, fat- loaded cells contained more a-tocopherol, and BDP-a-tocopherol was specifically localized into intracellular fat droplets. In cells incubated with BDP a-tocopherol, we found that fat loading decreased a-tocopherol release. Induced expression of TPP, which mediates vitamin E intracellular disposition under normal conditions, was not observed in fat loaded cells, further confirming vitamin E was trapped in fat. Livers of mice fed high fat diet had more vitamin E compared to controls. By further increasing vitamin E content of the high fat diet, we observed a reduction in liver size and liver fat in the high vitamin E group. Using a mouse metabolic chamber, we observed a slight reduction of oxygen consumption rate in the high vitamin E group compared to controls. Conclusions: Considered together, these findings imply that fat in the liver may produce unrecognized hepatic vitamin E sequestration, which could drive liver disease. These results are consistent with the possibility that increased vitamin E intake might, if begun at an early stage, restore vitamin E physiology, potentially decreasing or preventing progression of HS to NASH. Funding Sources: NIH intramural program (DK053213–14).